Specific recommendations for PROs and HRQoL assessment in allergic rhinitis and/or asthma: a GA(2)LEN taskforce position paper - Braido, F (2010)
The GA(2)LEN taskforce on Patient-Reported Outcomes (PROs) and Health-Related Quality of Life (HRQoL) published in 2009 a position paper concerning PROS and HRQoL assessment in clinical trials on allergy. Because of the specificity of this topic in asthma and rhinitis, specific recommendations are needed. The aim of this position paper is to define PROs and their meaning in asthma and rhinitis research, explore the available tools to provide criteria for a proper choice, identify patient-related factor which could influence PROs assessment, define specific recommendations for assessment, analysis and results spreading, underline the unexplored areas and unmet needs. PROs assessment is gaining increasing importance, and it must be performed with a rigorous methodological procedure and using validated tools. This approach enables to better understand patient-related factors influencing clinical trials and real-life management outcomes, identify patients subgroups that can benefit from specific treatment and management plan and tailor treatment to address PROs (not only physician-defined targets) to improve asthma and rhinitis management.